Peran Pengasuhan Terhadap Kepatuhan Pada Anggota Polisi Satuan Sabhara Dipolres X (Jurnal Insan Pendidikan dan Sosial Humaniora, 2023)
Parental care is inseparable from the morals and ways of educating children's behavior, how to make children have behavior that is in accordance with applicable rules and norms, both in the family environment and work environment. Quantitative research type with 85 respondents. .The measuring instrument in this study is a compliance scale, using a modification of measuring instruments from Pertiwi and Muminin (2020), with a total of 12 items, measuring instruments on the parenting scale in this study used modifications to measuring instrument instruments developed by Pertiwi and Muminin (2020) research with a total of 18 items from 27 items. The hypothesis in this study is "There is an effect between parenting and compliance in members of the Sabhara Police Unit at Police Station X". The statistical description test showed mean results on the parenting variable of 4.12, a median of 4.0 and a standard deviation of .45, on the compliance variable, a mean result of 4.46, a median of 4.54 and a standard deviation of 5.0. Based on the normality test with Kolmogrov Smirnov Residual, it is known that the monte carlo sig (2-tailed) value of 0.441 results can be interpreted as normal distributed data. The results of the linearity test obtained a significance value of 0.811, it shows that p > 0.05 which means that there is a linear relationship between the parenting variable and the compliance variable. Based on the correlation test, the correlation coefficient value of the parenting variable with compliance is .409** with a sig (2-tailed) level of 0.000 (p< 0.05) so that it can be stated that there is a positive relationship between parenting and compliance at police station x. The results of the study based on regression tests showed that parenting contributed 16.7% to compliance.